FORMULATION OPTIMIZATION OF SWAMP VEGETATION NATURAL DYES FOR DSSC USING SIMPLEX LATTICE DESIGN - Muhammad Rizki Azra; Tamrin Tamrin; Haisen Hower (Indonesian Physical Review, 2026)
Dye-sensitized solar cells (DSSC) are third-generation photovoltaic devices capable of using natural pigments as photosensitizers. This study aims to optimize the efficiency of DSSC by using formulations of a combination of natural dyes extracted from swamp vegetation: water hyacinth (Eichhornia crassipes), senduduk fruit (Melastoma malabathricum), and primrose willow (Ludwigia peruviana). These dyes, which are rich in chlorophyll, anthocyanins, and carotenoids, respectively, were formulated in different volume combinations using the Simplex Lattice Design (SLD) method. The experimental results show that the mixture of natural dyes can expand the absorption range of visible light wavelengths and enhance the performance of DSSC. The optimal dye combination, consisting of 1.827 mL water hyacinth and 3.173 mL senduduk fruit, yielded an efficiency of 0.050% with a desirability score of 1. This study highlights the potential of swamp vegetation as a sustainable and low-cost alternative for DSSC applications and demonstrates the effective use of statistical modeling to optimize dye formulations.